Responsiveness of two participation measures in an outpatient rehabilitation setting. (May 2013) - van der Zee, Carlijn H.; Baars-Elsinga, Annette; Visser-Meily, Johanna M.A.; Post, Marcel W.M.
Abstract Objective: The responsiveness of a new participation measure, the Utrecht Scale for Evaluation of Rehabilitation-Participation (USER-Participation) was compared with that of the Impact on Particpation and Autonomy (IPA). Furthermore, the concurrent validity of these two measures was assessed. Method: Participants were patients with brain injury or neuromuscular disease, who received occupational therapy as part of a multidisciplinary outpatient rehabilitation programme. They completed the IPA and the USER-Participation at the start and end of the programme, and at three-month follow-up. Responsiveness was analysed using the effect size (ES) and the standardized response mean (SRM). Results: Responsiveness figures were small to moderate (–0.4 to 0.5) and similar for the IPA and the USER-Participation. The USER-Participation showed a consistent result, with Frequency scores declining and Restriction and Satisfaction scores inclining over time, and the IPA showed mixed results, with the different domain scores both inclining and declining over time. Correlations between IPA and USER-Participation scales were all significant, but by far strongest for the USER-Participation Satisfaction scale (–0.64 to –0.81). Conclusion: The USER-Participation was at least as responsive as the IPA. Further, satisfaction with participation as measured with the USER-Participation is highly similar to the concept of autonomy in participation as measured with the IPA.